E-tivities and the connecting of e-learning experiences through deliberative feedback - Slevin, James (Tidsskrift for Universiteternes Efter- og Videreuddannelse (UNEV), 2006)
Første gang publiceret i UNEV nr. 9: Evaluering og feedback i netstøttet uddannelse, sept. 2006, red. Simon Heilesen. ISSN 1603-5518. This article examines the way in which e-learning is transforming the nature of social interaction in education. It begins by situating e-learning within the context of the transitions taking place in everyday life and in the distinctive qualities of social organization over the past four or five decades. One of the most important aspects of social interaction in education is the giving and receiving of feedback. Focusing on Gilly Salmon’s work on e-tivities and e-moderating, the article goes on to present a critical analysis of the refashioning of feedback in the organization, design and delivery of online collaborative learning activities. The article concludes that an ongoing critical engagement with the challenges concerning the impact of net-media on learning involves understanding how e-learning is inseparably linked to broader societal transitions, fundamental changes in our information environments, and major shifts in the way that we approach teaching and learning.